Bifunctional Polyene Cyclizations: Synthetic Studies on Pimarane Natural Products. Issue 48 (22nd July 2021) - Feilner, Julian M.; Plangger, Immanuel; Wurst, Klaus; Magauer, Thomas
Abstract: Polyene cyclizations generate molecular complexity from a linear polyene in a single step. While methods to initiate these cyclizations have been continuously expanded and improved over the years, the majority of polyene substrates are still limited to simple alkyl‐substituted alkenes. In this study, we took advantage of the unique reactivity of higher‐functionalized bifunctional alkenes. The realization of a polyene tetracyclization of a dual nucleophilic aryl enol ether involving a transannular endo ‐termination step enabled the total synthesis of the tricyclic diterpenoid pimara‐15‐en‐3α‐8α‐diol. The highly flexible and modular route allowed for the preparation of a diverse library of cyclization precursors specifically designed for the total synthesis of the tetracyclic nor ‐diterpenoid norflickinflimiod C. The tetracyclization of three diversely substituted allenes enabled access to complex pentacyclic products and provided a detailed insight into the underlying reaction pathways. Abstract : The biosynthesis of pimaranes is based on two consecutive cyclization reactions of the linear polyene geranylgeranyl diphosphate. In contrast, our synthetic studies on pimaranes involve a tetracyclization reaction of a dual nucleophilic aryl enol ether. The modified isoprene enabled a transannular end o‐termination step and rapid assembly of the natural product pimara‐15‐en‐3α‐8α‐diol.